2016
DOI: 10.1158/1541-7786.mcr-15-0418
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ANRIL–Polycomb Complexes–CDKN2A/B/ARF Genes in Breast Tumors: Identification of a Two-Gene (EZH2/CBX7) Signature with Independent Prognostic Value

Abstract: ANRIL, a long noncoding RNA (lncRNA), has recently been reported to have a direct role in recruiting polycomb repressive complexes PRC2 and PRC1 to regulate the expression of the p15/CDKN2B-p16/CDKN2A-p14/ARF gene cluster. Expression analysis of ANRIL, EZH2, SUZ12, EED, JARID2, CBX7, BMI1, p16, p15, and p14/ARF genes was evaluated in a large cohort of invasive breast carcinomas (IBC, n ¼ 456) by qRT-PCR and immunohistochemistry (IHC) was performed on CBX7, EZH2, p14, p15, p16, H3K27me3, and H3K27ac. We observe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 45 publications
2
64
0
1
Order By: Relevance
“…In another study, the P16 positive patients had a better response to chemotherapy than breast cancer patients with P16 negative. These findings support that the P16 may be used as a prognostic factor for the consequence and response to the treatment of the patients (Meseure et al, ).…”
Section: Discussionsupporting
confidence: 79%
“…In another study, the P16 positive patients had a better response to chemotherapy than breast cancer patients with P16 negative. These findings support that the P16 may be used as a prognostic factor for the consequence and response to the treatment of the patients (Meseure et al, ).…”
Section: Discussionsupporting
confidence: 79%
“…A recent study measured mRNA levels of the gene encoding ANRIL in 456 breast carcinomas tissues and found that ANRIL mRNA expression was higher in breast carcinomas tissues than in normal breast tissues, which was exclusively and weakly correlated with ER and PR status and showed a complex association with epithelial–mesenchymal transition markers. [31] We determined ANRIL expression in the plasma of patients with BC and found that its expression was surprisingly higher in patients with TNBC than in patients with NTNBC. These findings prompted us to determine the diagnostic value of ANRIL in TNBC, which has not been performed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Similar in breast cancer, several lncRNAs such as ANRIL or UCA1 and snaR were revealed as upregulated and strongly associated with tumor progression or poor prognosis in previous studies. 12,13,[26][27][28] However, as breast cancer is an extremely heterogenic disease, these knockdown processes may not result as identical based on tumor subtypes or characteristics. Therefore, the study of biological functions of lncRNA should be conducted differently according to the subtype of breast cancer.…”
Section: Discussionmentioning
confidence: 99%